Factor Proportions, Linkages and the Open Developing Economy - Riedel, James (The Review of Economics and Statistics, 1975)
The purpose of this paper is to examine the theoretical rationale underlying the growth of footloose, import-dependent industry observed in many of the most successful developing countries (Hong Kong, Taiwan, S. Korea, for example). A second objective is to develop empirical formulations appropriate for analyzing the resource allocation consequences of a footloose industrial structure in a developing country. It is argued that previous applications of input-output techniques to factorintensity measurement have in general ignored the implications of trade in intermediate inputs. The Leontief test of the Heckscher-Ohlin trade theory is perhaps the first and certainly the most widely adopted application of input-output techniques to the measurement of the factor intensity of production. The first section of this paper will attempt to demonstrate that the procedure developed by Leontief is not strictly appropriate in an open economy which utilizes imported as well as domestically supplied inputs. An alternative formulation is developed in this paper, which when compared to the Leontief formulation yields a measure of the domestic resource cost or saving resulting from the use of imported rather than domestically produced inputs. (This abstract was borrowed from another version of this item.)